Degradation of Cyanoacrylic Acid‐Based Organic Sensitizers in Dye‐Sensitized Solar Cells. Issue 7 (14th June 2013) - Chen, Cheng; Yang, Xichuan; Cheng, Ming; Zhang, Fuguo; Sun, Licheng
Abstract Organic dyes have become widely used in dye‐sensitized solar cells (DSSCs) because of their good performance, flexible structural modifications, and low costs. To increase the photostability of organic dye‐based DSSCs, we conducted a full study on the degradation mechanism of cyanoacrylic acid‐based organic sensitizers in DSSCs. The results showed that with the synergy between water and UV light, the sensitizer could desorb from the TiO2 surface and the cyanoacrylic acid unit of the sensitizer was transformed into the aldehyde group. It was also observed that the water content had a great effect on the degradation process. Our experiments conducted using 18O‐labeled water demonstrated that the oxygen atom of the aldehyde group identified in the degraded dye came from the solvent water in the DSSCs. Therefore, controlling the water content during DSSC fabrication, good sealing of cells, and filtering the UV light are crucial to produce DSSCs that are more durable and robust.